Ethical and legal challenges in nanomedical innovations: a scoping review - Wasti, Sophia; Lee, Il Ho; Kim, Sumin; Lee, Jae-Hyun; Kim, Hannah (Frontiers in Genetics, 2023)
Background: Rapid advancements in research and development related to nanomedical technology raise various ethical and legal challenges in areas relevant to disease detection, diagnosis, and treatment. This paper aims to outline the existing literature, covering issues associated with emerging nanomedicine and related clinical research, and identify implications for the responsible advancement and integration of nanomedicine and nanomedical technology throughout medical networks in future. Methods: A scoping review, designed to cover scientific, ethical, and legal literature associated with nanomedical technology was conducted, generating 27 peer-reviewed papers published between 2007 and 2020. Results: Results indicate that papers referencing ethical and legal issues related to nanomedical technology were concerned with five key areas - 1) harm exposure and potential risks to health, 2) consent to nano-research, 3) privacy, 4) access to nanomedical technology and potential nanomedical therapies, and 5) classification of nanomedical products in relation to the research and development of nanomedical technology. Conclusions: This review of the literature suggests that there are few practical solutions that are comprehensive enough to allay the ethical and legal concerns surrounding research and development in fields related to nanomedical technology, especially, as it continues to evolve and contributes to future innovations in medicine. It is also made clearly apparent that a more coordinated approach is required to ensure the worldwide standards of practice governing the study and development of nanomedical technology, although talks about the regulation of nanomedical research are mainly confined to systems of governance in the United States (US), throughout the literature.